Hospital-based specialist palliative care compared with usual care for adults with advanced illness and their caregivers: a systematic review - Adejoke O Oluyase; Irene J Higginson; Deokhee Yi; Wei Gao; Catherine J Evans; Gunn Grande; Chris Todd; Massimo Costantini; Fliss EM Murtagh; Sabrina Bajwah (National Institute for Health Research, 2021)
Background: Most deaths still take place in hospital; cost-effective commissioning of end-of-life resources is a priority. This review provides clarity on the effectiveness of hospital-based specialist palliative care. Objectives: The objectives were to assess the effectiveness and cost-effectiveness of hospital-based specialist palliative care. Population: Adult patients with advanced illnesses and their unpaid caregivers. Intervention: Hospital-based specialist palliative care. Comparators: Inpatient or outpatient hospital care without specialist palliative care input at the point of entry to the study, or community care or hospice care provided outside the hospital setting (usual care). Primary outcomes: Patient health-related quality of life and symptom burden. Data sources: Six databases (The Cochrane Library, MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO and CareSearch), clinical trial registers, reference lists and systematic reviews were searched to August 2019. Review methods: Two independent reviewers screened, data extracted and assessed methodological quality. Meta-analysis was carried out using RevMan (The Cochrane Collaboration, The Nordic Cochrane Centre, Copenhagen, Denmark), with separate synthesis of qualitative data. Results: Forty-two randomised controlled trials involving 7779 participants (6678 patients and 1101 unpaid caregivers) were included. Diagnoses of participants were as follows: cancer, 21 studies; non-cancer, 14 studies; and mixed cancer and non-cancer, seven studies. Hospital-based specialist palliative care was offered in the following models: ward based (one study), inpatient consult (10 studies), outpatient (six studies), hospital at home or hospital outreach (five studies) and multiple settings that included hospital (20 studies). Meta-analyses demonstrated significant improvement favouring hospital-based specialist palliative care over usual care in patient health-related quality of life (10 studies, standardised mean difference 0.26, 95% confidence interval 0.15 to 0.37; I2 = 3%) and patient satisfaction with care (two studies, standardised mean difference 0.36, 95% confidence interval 0.14 to 0.57; I2 = 0%), a significant reduction in patient symptom burden (six studies, standardised mean difference -0.26, 95% confidence interval -0.41 to -0.12; I2 = 0%) and patient depression (eight studies, standardised mean difference -0.22, 95% confidence interval -0.34 to -0.10; I2 = 0%), and a significant increase in the chances of patients dying in their preferred place (measured by number of patients with home death) (seven studies, odds ratio 1.63, 95% confidence interval 1.23 to 2.16; I2 = 0%). There were non-significant improvements in pain (four studies, standardised mean difference -0.16, 95% confidence interval -0.33 to 0.01; I2 = 0%) and patient anxiety (five studies, mean difference -0.63, 95% confidence interval -2.22 to 0.96; I2 = 76%). Hospital-based specialist palliative care showed no evidence of causing serious harm. The evidence on mortality/survival and cost-effectiveness was inconclusive. Qualitative studies (10 studies, 322 participants) suggested that hospital-based specialist palliative care was beneficial as it ensured personalised and holistic care for patients and their families, while also fostering open communication, shared decision-making and respectful and compassionate care. Limitation: In almost half of the included randomised controlled trials, there was palliative care involvement in the control group. Conclusions: Hospital-based specialist palliative care may offer benefits for person-centred outcomes including health-related quality of life, symptom burden, patient depression and satisfaction with care, while also increasing the chances of patients dying in their preferred place (measured by home death) with little evidence of harm. Future work: More studies are needed of populations with non-malignant diseases, different models of hospital-based specialist palliative care, and cost-effectiveness. Study registration: This study is registered as PROSPERO CRD42017083205. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 9, No. 12. See the NIHR Journals Library website for further project information.